Overtraining phenomena: Expert and athlete perspectives on pathogenic sport involvement - Richardson, S. O. (2005)
The purpose of this research project was to provide an in-depth account of elite athletes' experiences of, and experts` perspectives on, overtraining and its negative outcomes. I conducted interviews with athletes and sports experts, including coaches, sport doctors, scientists, and psychologists across a variety of sports. The interviews were focussed on identifying personal and situational risk factors for overtraining behaviours and outcomes. This thesis includes discussions of the responses to the interviews from the athletes` and the experts` perspectives, with distinct approaches to analysing and presenting the interview data from these two groups` different perspectives. For the 14 experts, I carried out inductive content analyses of the interviews and presented the results in a tree-structure showing the major categories, subcategories, and raw data themes emerging from the data. For the 13 athletes, I used a narrative approach to analysing and presenting their stories, which I aggregated into three core tales, represented by three constructed fictional athletes. From the athletes` stories, I found support for the perspectives presented by the experts. I also uncovered, however, unique accounts of overtraining experiences that provided insight into the intra-psychic conflicts, sometimes obsessive-compulsive features, and complicated relationships of the not-as-perfect-as-perceived-to-be athletes. Taken together, both sets of interviews revealed that overtraining behaviours are significant issues in most sports, whether skill- or effort-based, which may go against traditional conceptions of overtraining. In the general discussion, I present a descriptive model of overtraining risks and outcomes, which came together from the synthesis of the athlete and expert interview results, and, finally, I discuss implications for professional practice and make suggestions for future research. http://wallaby.vu.edu.au/adt-VVUT/uploads/approved/adt-VVUT20060424.162044/public/02ch1-4.pdf http://wallaby.vu.edu.au/adt-VVUT/uploads/approved/adt-VVUT20060424.162044/public/03ch5.pdf http://wallaby.vu.edu.au/adt-VVUT/uploads/approved/adt-VVUT20060424.162044/public/04ch6.pdf http://wallaby.vu.edu.au/adt-VVUT/uploads/approved/adt-VVUT20060424.162044/public/05ch7-end.pdf http://wallaby.vu.edu.au/adt-VVUT/uploads/approved/adt-VVUT20060424.162044/public/06figure2.pdf